MEWUJUDKAN PENDIDIKAN DALAM KELUARGA MUSLIM YANG VISIONER - Lisnawati Lisnawati (Universitas Muhammadiyah Ponorogo, 2018)
Family is the smallest unit in society and as one of the social institutions in society. Family as a social system has the duty and function to make the system works. The function of education becomes one of the most important functions of a family. Education of family provides the first experience that is an important factor in the children's personal development, as well as the first and main education of the children. Islam as a religion that regulates all aspects of human life does neglect out to regulate about education in the family. Islamic education is part of an effort to instill the values of Islamic teachings in its followers. Islam places the family as the foundation of Islamic values. Activities of islamic education in order to build the muslim personality have to start early, in the family environment. Visionary families will make their lives more organized and prepared for the challenges of life in the future, including will be able to build a family that generates a superior generation. To realize the education of visionary muslim family, Islam guides to start early, even since choosing a partner of life, children care since the womb, continuously going on the process of growth and education in the family.